Habitat selection of Ortolan Buntings Emberiza hortulana on forest clear-cuts in northern Sweden - Percival, Julianna Anne; Dale, Svein (Ornis Svecica, 2016)
Ortolan Buntings Emberiza hortulana in Sweden used to occur mainly in farmland. Nowadays, a large proportion of the remaining population is found on forest clear-cuts in northern Sweden. Few studies have identified the types of clear-cuts that Ortolan Buntings prefer and whether these habitats are used for both breeding and foraging. We recorded presence and abundance of ortolan buntings on clear-cuts in Västerbotten County, northern Sweden. We sampled 123 clear-cuts (present N = 48, absent N = 75; total of 93–100 territories) and our results showed that clear-cut size, the number of remaining trees, bare soil percentage (≥10%) and narrow-leaved grass vegetation had a positive influence on ortolan bunting occupancy. The number of territories on clear-cuts was positively related to clear-cut size and number of remaining trees. Proximity to nearby farmland did not influence occupancy on clear-cuts. Behavioural observations indicated that the forest clear-cuts were used for both nesting and feeding. We discuss these results in relation to forest management policies and conservation of the ortolan bunting.